Analysis of Students' Motivation and Achievement: Comparing BAHASA INGGRIS Textbook and Nias Local Wisdom Materials: Analisis Motivasi dan Prestasi Siswa: Membandingkan Buku Ajar BAHASA INGGRIS dan Materi Kearifan Lokal Nias - Zebua, Innes Lestari; Zebua, Elwin Piarawan; Laoli, Adieli; Zega, Riswan (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
English reading skills are essential for academic success, fostering comprehension, critical thinking, and motivation. Engaging reading materials, particularly those reflecting cultural relevance, like Nias local wisdom, enhance intrinsic motivation and learning achievement. This research uses a mixed-methods approach to assess textbook content with Nias-based texts to assess their motivational impact. Using a Sequential Explanatory Design, the study combines quantitative and qualitative methods for comprehensive insights. Quantitative tests measure reading comprehension and motivation, while qualitative interviews explore students' perceptions. Data integration ensures robust findings, guiding effective educational practices at SMA Negeri 1 Gunungsitoli. The research analyzed texts from the BAHASA INGGRIS textbook ("Little Red Riding Hood") and Nias local wisdom ("Warrior of Sun Hill"). Students scored higher on the Nias text (mean 83.1 vs. 81.9), indicating greater engagement. Interviews with the Nias text revealed stronger intrinsic motivation, such as curiosity, involvement, and challenge. Extrinsic factors, like grades and compliance, were less influential but still relevant. A readability analysis showed "Little Red Riding Hood" as more straightforward, making it suitable for younger readers. The study highlights that culturally relevant texts, like Nias wisdom-based materials, significantly boost students' motivation, engagement, and academic performance, underscoring the importance of incorporating intrinsic motivators into English reading curricula.